Serotonin Reuptake Inhibitors are Associated with Less Amyloid‐β Burden Spatial Extent in Military Veterans with only PTSD, but not with TBI or Comorbid PTSD/TBI: Preliminary PET Findings from ADNI‐DOD Project. (20th December 2022) - Chen, Kewei; Goradia, Dhruman D.; Chen, Yinghua; Luo, Ji; Devadas, Vivek; Jagust, William J.; Mackin, R Scott; Su, Yi; Landau, Susan M.; Weiner, Michael W.; Reiman, Eric M.
Abstract: Background: Some but not all studies suggested an association of serotonin reuptake inhibitors (SRIs) with a reduction in "magnitude" of amyloid‐β (Aβ) plaque burden. Using PET images from ADNI‐DOD and a voxel‐based Majority Count Algorithm (MCA), we demonstrated that cognitively unimpaired veterans with post‐traumatic stress disorder (PTSD) had significantly more cerebral voxels with lower rather than higher florbetapir standard uptake value ratios (voxel‐based P<0.05), reflecting Aβ burden reduction in "spatial extent" [Chen, AAIC 2018]). We postulated that this finding might relate their SRI use. Here, we investigate the impact of SRI use on the spatial extent of Aβ burden among ADNI‐DOD veterans with PTSD, comorbid PTSD and traumatic brain injury (TBI), and TBI. Methods: Statistical Brain Mapping (SPM12) adjusted for age, MMSE, education and APOE4 allele, a voxel‐based P<0.05 threshold, and MCA which is free of multi‐comparisons (Stern, NEJM, 2019) were used to compare the greater versus lower number of cerebral voxels with higher Aβ burden in SRI non‐users versus users in 6 groups: 1) PTSD (n=76), 2) PTSD or TBI (n=115), 3) comorbid PTSD/TBI or TBI (n=126), 4) PTSD, PTSD/TBI or TBI (n=202), 5) PTSD/TBI (n=87) and 6) TBI (n=39). Results: SRI non‐users had a significantly larger number of cerebral voxels with higher Aβ burden than users in the first four groups: 1) 28, 539 in non‐users versus 70 in users (voxel count ratio VCR=551) in PTSD; 2) 3, 573 versus 21 (VCR=170) in PTSD or TBI; 3) 22, 927 versus 1, 162 (VCR=20) in comorbid PTSD/TBI or TBI; and 4) 7, 569 versus 1, 481 (VCR=5) in PTSD, comorbid PTSD/TBI or TBI, MCA p<0.001 for all 4 groups. In contrast, 5) SRI non‐users and users did not differ in the number of cerebral voxels with higher Aβ burden in PTSD/TBI (3, 209 versus 4, 027, VCR=1, MCA p=0.68); and 6) non‐users had a significantly smaller number of cerebral voxels than users with higher Aβ burden in TBI (60 versus 11, 715 VCR=0.005, MCA p<0.001). Conclusion: This study showed SRIs' association with spatially less extensive Aβ burden in PTSD, more extensive Aβ burden in TBI, and intermediate/opposing effects in other combinations. Finding conformation and mechanism clarification are needed.